EDUCATIONAL ANALYSIS OF THE TEACHING OF PARENTING TRAINING (JARLATSUH) IMMIGRATION POLYTECHNIC IN ONLINE LEARNING AS AN OPTIMIZATION OF THE LEARNING SYSTEM - Moch Zidane Hatta Hasibuan; Muhammad Itsar Muqarab (Polteknik Imigrasi, 2023)
Education is a crucial aspect, as mandated in the Constitution of the Republic of Indonesia. The application of education is generally different, but the goal is the same, namely, to educate the Indonesian nation. The Immigration Polytechnic, as a polytechnic under the auspices of the Ministry of Law and Human Rights, implements the Training and Care Lesson System (JARLATSUH). This learning system must be adaptable as a stimulant for the embodiment of industrial technology 4.0 COVID-19. The analysis that we did was to determine the effectiveness of applying online learning and solutions in developing the JARLATSUH learning system